Study of Prescribing Pattern, Identification of Drug Related Problems and Therapeutic Intervention in Cardio Vascular Diseases (CVD) Patients - Biradar, S M.; Naveed, Mohammed; Sai, P. Keerthi; Raju, H. Pruthvi; Kumar, A. Harish; Ambali, Anand P.; Sorangavi, Vijaya; Shivakumar, B.; Kalyane, N V. (Journal of Drug Delivery and Therapeutics, 2018)
Cardiovascular disease (CVD) is a disorder of heart and blood vessels. CVD is one of the major causes of deaths in India, which contributed around 30 to 40%. The aim of the study was to study the prescribing pattern of drugs, identification of drug related problems and therapeutic intervention in CVD patients. A hospital based prospective and observational study was carried out for a period of nine months in a south Indian tertiary care hospital. Among 120 selected patients, 79 were male (65.83%) and 41 were female (34.16%), more number of patients (35) were between the age group of 55-64 (29.16%) of which 27 were males & 8 were females, and very less number of patients (6) were between the age group 85-94 (5%) of which all the 6 were male. Hypertension is the most commonest and dominant disorder, which affected 47(39.16%) patients, in which 30 were male (25%) and 17 were female (14.16%). Most common risk factor is HTN followed with smoking and diabetes of 45 patients (37.5%). The most often prescribed pattern adopted in CVD is Dual therapy, it is most frequently used therapy 50 (41.66%) and quadruple therapy is less frequently 6(6.5%) used. The diuretics and calcium channel blocker combination were maximally prescribed class of drugs as a dual therapy. A total of 47 drug-drug interactions were found, among 12 were major, 15 were moderate and 20 were minor interactions. Clinical pharmacist has intervened with the help of other health care professionals in order to reduce the risk factor and minimise the drug-drug interactions. The study provides the benefits of presence of clinical pharmacist in a hospital setting, in order to prevent the medication related errors and provide the expertise pharmacotherapy opinion in CVD patients, which improves the patient compliance. Hence study justifies a need of active collaboration between clinical pharmacist, physician and other health care professionals for the better management of CVD patients. Keywords: Prescribing Pattern; Cardio Vascular Diseases; Drug Related Problems; Therapeutic Intervention.